Acute generalized exanthematous pustulosis x Von Zumbusch's pustular psoriasis: A diagnostic challenge in a psoriatic patient - Aline Soares de Sousa; Osório Alves Corrêa de Castro Lara; Francine Papaiordanou; Gláucia Silva Simioni Marchioro; Antonio José Tebcherani (Sociedade Brasileira de Dermatologia, 2015)
AbstractSevere cutaneous drug reactions include a wide spectrum of clinical manifestations ranging from mild morbilliform cutaneous rash, to severe forms of hypersensitivity. Special attention is given in this report to the acute generalized exanthematous pustulosis (AGEP), induced in 90% of cases by the use of systemic drugs, especially aminopenicillins and macrolides. The incidence of the disease is low, 1-5 cases per million patients / year. The main differential diagnosis is Von Zumbusch's Pustular Psoriasis. The prognosis is generally good and the disease self limited, after withdrawal of the triggering drug. In this report the authors describe a case of AGEP, triggered by ceftriaxone in a patient with psoriasis vulgaris.